The modern cottage - Cole, Mary Margaret (My University, 1905)
Introduction: In this advanced age of the world our attention is drawn more and more to the home as a means of advancement – mentally, morally, and otherwise and we are forced to realize that the largest part of this advancement is due to the wife’s and mother’s influence. It is for this reason that I turn my attention to the home – the mother’s domain and most strongly do I wish to impress upon my readers that every convenience given to the mother will be shared equally by the other members of the family by lessening mother’s hours of toil thus giving her more time to spend with her family. I begin my discussion with the kitchen which should be the best equipped room in the house while in most cases it is actually the poorest. It should be nearly square and need have no more than 150 sq. feet of floor space. In this room convenience must be the ruling theme. Hard wood as oak, maple, ash; and walnut are desirable for flooring as they will not splinter, shrink or warp easily: but most of these are very expensive.
The interior of the modern cottage
Citation: Cole, Mary Margaret. The modern cottage. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Wood Work; Lime Finish Walls; Zink Sink; Theses; Manuscripts (documents)